2017
DOI: 10.3847/1538-4357/aa9b34
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Studies of Solar White-light Flares and Comparisons with Superflares on Solar-type Stars

Abstract: Recently, many superflares on solar-type stars have been discovered as white-light flares (WLFs). The statistical study found a correlation between their energies (E) and durations (τ ): τ ∝ E 0.39 (Maehara et al. 2015, EP&S, 67, 59), similar to those of solar hard/soft X-ray flares: τ ∝ E 0.2−0.33 . This indicates a universal mechanism of energy release on solar and stellar flares, i.e., magnetic reconnection. We here carried

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
125
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 73 publications
21
125
2
Order By: Relevance
“…In both cases, a weak correlation is found considering only the M stars. In the Kepler band we find that Article number, page 18 of 25 kep,flare , which is significantly different from the relation found by Namekata et al (2017). In X-rays we find a steeper relation (t xray =E 0.52 xray,flare ) than the one found for solar flares (t xray =E 0.2−0.33 xray,flare ; Veronig et al 2002).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In both cases, a weak correlation is found considering only the M stars. In the Kepler band we find that Article number, page 18 of 25 kep,flare , which is significantly different from the relation found by Namekata et al (2017). In X-rays we find a steeper relation (t xray =E 0.52 xray,flare ) than the one found for solar flares (t xray =E 0.2−0.33 xray,flare ; Veronig et al 2002).…”
Section: Discussioncontrasting
confidence: 84%
“…In X-rays we find a steeper relation (t xray =E 0.52 xray,flare ) than the one found for solar flares (t xray =E 0.2−0.33 xray,flare ; Veronig et al 2002). These differences are likely due to the poor statistical sample of superflares analyzed in this paper and the limited range of emitted energy (32.9≤log(E K2,flare )≤34.7 in our sample, 33≤log(E K2,flare )≤36 in Namekata et al (2017)). We however extend the results obained by Hawley et al (2014) on the flares occurring in GJ 1243, where the energy of the observed flares reached 10 33 erg in the Kepler band, smaller than most of the flares analyzed in this paper.…”
Section: Discussionmentioning
confidence: 83%
“…The timescales and energies of the two GJ 1243 flare events are strikingly similar to the largest solar flares (Woods et al 2004); thus, HST-1 and HST-2 may be suitable for establishing connections and differences (e.g., in the slow rise and decay of Ca II K) between dMe and dG flares. Recently, Namekata et al (2017) compared the durations and energies of flares on GJ 1243 (from Kepler ) to whitelight flares on the Sun (from SDO/HMI). They found that both GJ 1243 and the Sun exhibited similar power-law scalings between flare energy and duration as found in Maehara et al (2015), but that for a given duration, the flares on GJ 1243 were 10x larger energy (all bolometric flare energies were calculated assuming a blackbody; see Section 9).…”
Section: Future Modeling Directions and Connection To Dg Flaresmentioning
confidence: 99%
“…One important exception is the lack of the detection of QPP in solar flares in the white light emission, while QPP are confidently detected in this band in stellar flares. However, we should point out that solar flares are rarely detected in the white light anyway, see [6] for a recent discussion.…”
Section: Introductionmentioning
confidence: 99%